Characterization of the Robinow syndrome skeletal phenotype, bone micro‐architecture, and genotype–phenotype correlations with the osteosclerotic form. Issue 11 (5th September 2020) - Shayota, Brian J.; Zhang, Chaofan; Shypailo, Roman J.; Mazzeu, Juliana F.; Carvalho, Claudia M. B.; Sutton, V. Reid
ABSTRACT: Robinow syndrome (RS) is a genetically heterogeneous skeletal dysplasia with recent reports suggesting an osteosclerotic form of the disease. We endeavored to investigate the full spectrum of skeletal anomalies in a genetically diverse cohort of RS patients with a focus on the bone micro‐architecture. Seven individuals with molecularly confirmed RS, including four with DVL1 variants and single individuals with variants in WNT5A, ROR2, and GPC4 underwent a musculoskeletal focused physical examination, dual‐energy X‐ray absorptiometry (DEXA) scan, and high‐resolution peripheral quantitative computed tomography (HR‐pQCT). Skeletal examination revealed variability in limb shortening anomalies consistent with recent reports. DEXA scan measures revealed increased total body bone mineral density (BMD) (3/7), cranial BMD (5/7), and non‐cranial BMD (1/7). Cranial osteosclerosis was only observed in DVL1 ‐RS (4/4) and GPC4 ‐RS (1/1) subjects and in one case was complicated by choanal atresia, bilateral conductive hearing loss, and cranial nerve III, VI, and VII palsy. HR‐pQCT revealed a unique pattern of low cortical BMD, increased trabecular BMD, decreased number of trabeculations, and increased thickness of the trabeculations for the DVL1 ‐RS subjects. The spectrum of skeletal anomalies including the micro‐architecture of the bones observed in RS has considerable variability with some osteosclerosis genotype–phenotype correlations more frequent with DVL1 variants.